Clinical dermatology - Weller, Richard P. J. B.; Hunter, Hamish J. A.; Mann, Margaret W. (John Wiley & Sons Inc., 2015)
The best-selling text has been completely revised and revitalised in this fifth edition, with the authors once again encouraging general practitioners, medical students, general physicians and early stage dermatology specialist trainees and interns to relish the unique challenge of diagnosing and treating skin conditions. Clinical Dermatology, 5th edition contains over 400 high quality pictures and diagrams combined with colourful phrases to illustrate and entertain as it teaches. The book has established a reputation as a 'way of learning' and as an accessible guide to the subject for the a.